Tsunami Disaster Mitigation Based on Eco-Action and Community Participation in Katapiang Village, Pariaman - Tarigan, Vita Cita Emia; Mulyadi, Mahmud; Hafizhul Khair AM; Yulida, Devi; Ferdi; Zimtya Zora (Mahadi: Indonesia Journal of Law, 2025)
Katapiang Village faces a high risk of tsunami disaster, given its location on the Indo-Australian and Eurasian plate subduction zones. The majority of Katapiang Village residents depend on the fisheries and agriculture sectors, which makes them vulnerable to the impacts of tsunamis, especially if infrastructure and livelihoods are damaged. Although the government has attempted physical mitigation such as evacuation routes, public and official awareness of the importance of environmental conservation as part of disaster mitigation is still low. One solution offered is an ecosystem-based approach, such as planting mangroves that can function as natural protection against tsunamis. This study aims to examine tsunami disaster mitigation efforts in Katapiang Village, Padang Pariaman Regency, through an eco-action approach and community participation. This study uses a literature study method, with data sources in the form of journals, activity reports, news articles, and documents from local organizations such as JEMARI Sakato and publications from the Regional Disaster Management Agency (BPBD). Eco-action-based mitigation through planting and maintaining mangrove forests is considered potential to strengthen coastal protection against tsunamis, while increasing environmental awareness and economic empowerment of residents. The combination of ecological and participatory approaches is considered relevant and necessary as a locally based adaptive strategy in building the resilience of Nagari Katapiang to disasters.